EVALUATING THE EFFECTIVENESS OF INNOVATION IMPLEMENTATION AT TRANSPORT ENTERPRISES UNDER CONDITIONS OF UNCERTAINTY - Oksana O. Karpenko; Olha O. Kravchenko; Olena M. Palyvoda; Svitlana M. Semenova (Academy Review)
In the conditions of economic uncertainty associated with war, the task of developing and applying new approaches to assessing the economic efficiency and feasibility of introducing innovations at transport enterprises has become more urgent. In the presented study, a mental model for the formation of the effects of innovations was developed based on scenarios that describe existing relationships and trends, with the aim of incorporating them into the planning of innovative activities at a transport enterprise using PJSC Ukrzaliznytsia as an example. The authors have demonstrated that, under current conditions, scenario modeling is advisable for forecasting innovative development. Based on the expert survey, a system of scenarios for the implementation of the innovative project was developed: «Innovative growth», «Insufficient demand», «Insufficient supply», «Resource conservation». The study evaluated the potential effectiveness of introducing innovations to improve transport (railway) infrastructure under the «Insufficient demand» and «Insufficient supply» scenarios for PJSC Ukrzaliznytsia. It was calculated that, under the «Insufficient demand» scenario, the efficiency of innovation would be negative but with a tendency towards further growth from -9.4% in 2025 to -11.8% in 2029. Under the «Insufficient supply» scenario, a negative result from the introduction of innovations was also obtained, but with a tendency to decrease from -0.4% in 2025 to -0.1% in 2029, which would lead to an increase in the level of transport demand from 76.81% in 2025 to 89.23% in 2029. It was determined that, under current conditions, the scenario «Insufficient supply» would be more effective as its implementation would ensure an increase in the level of satisfaction of transportation needs through increased funding for the innovative project. The analysis of scenarios showed that it is possible to reduce the probability of unwanted effects by implementing an effective planning system and using modern financing mechanisms for innovative activities of transport enterprises.